Design of a New Type of Arm Joint Training Instrument with Multi-posture and Multi-motion Forms for Family Use - Wenjun Xu; Jianfeng Zhou; Liwen Zheng; Yuzhen Lin; Huifen Zhu (Jixie chuandong)
Aiming at the further acceleration of the aging speed in China， and considering the lack of effective exercise for the elderly， their shoulders， elbows and wrist joints often suffer from soreness， pain， and other problems. Thus， a new type of arm joint training instrument with multi-posture and multi-motion forms for family use is developed. Through theoretical design and calculation， and based on NX， a forward kinematic analysis and comparison of the four-bar mechanism without rapid return is conducted， 3 sets of rod length parameters (corresponding to 2 attitudes， 3 different motion forms， 9 different motion parameters respectively) are determined as a design scheme， and the force balance and load change analysis of the arm joint training equipment are carried out by the design scheme. Finally， according to the theoretical design calculation and the dynamic simulation analysis data of the NX virtual prototype， the performance of the physical prototype of the training instrument is trial-produced and tested. The test results show that the training instrument is safe， reliable and comfortable， and the human shoulders， elbows， wrists and waist joints can be better trained.